2016
DOI: 10.1111/jfpp.12746
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, Microbiological, Color and Textural Changes in Nile Tilapia (Oreochromis niloticus) Fillets Sterilized by Ozonated Water Pretreatment During Frozen Storage

Abstract: To assess the impact of ozonated water pretreatment on fish quality, Nile tilapia fillets were sterilized by 4.5 mg/L ozone‐containing water for 30 min and stored at −18 ± 1C for 180 days. Untreated fillets were used as controls. Quality changes during storage were assessed by chemical, microbiological analysis, color and texture measurements in both groups. The results showed that the pH did not significantly differ in both groups at various time points during storage and did not exhibit a significant correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…The decreases in hardness and cohesiveness were possibly due to the accelerated oxidation of proteins by the increasing concentration of RONS generated in PFL. A decrease in the hardness and comparable TPA of beef, black sea bream and Nile tilapia have also been reported during the thawing process with PFW, immersing in OFW and OFW combined with tea polyphenol [5] , [12] , [60] .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The decreases in hardness and cohesiveness were possibly due to the accelerated oxidation of proteins by the increasing concentration of RONS generated in PFL. A decrease in the hardness and comparable TPA of beef, black sea bream and Nile tilapia have also been reported during the thawing process with PFW, immersing in OFW and OFW combined with tea polyphenol [5] , [12] , [60] .…”
Section: Resultsmentioning
confidence: 83%
“…The textural profile of muscle foods is usually associated with species, muscle fibre density, fat and protein contents and water-holding capacity, and oxidation-induced water loss can reduce the water-holding capacity by damaging the membrane structural integrity of muscles fibres [59] , [60] . The hardness often substituted by firmness relates to the peak force during the first compression cycle or first bite, cohesiveness measures the rate, at which the muscle disintegrate during mastication, adhesiveness corresponds to the work required to overcome the attractive forces between muscle surface and other surfaces that it is in contact with, springiness relates to the recovery height of the muscle between the end of the first bite and start of the second bite, while chewiness measures the energy required for mastication [60] , [61] . The decreases in hardness and cohesiveness were possibly due to the accelerated oxidation of proteins by the increasing concentration of RONS generated in PFL.…”
Section: Resultsmentioning
confidence: 99%
“…Gumminess is defined as the force needed to disintegrate a semisolid sample to a steady state of swallowing, and is calculated as hardness × cohesiveness. Chewiness represents the work required to masticate a solid sample to a steady state of swallowing, which is calculated as hardness × cohesiveness ×springiness (Zhao et al., 2017). In the present study, Figures 3c,d show decreasing trends similar to that of hardness and springiness of L. vannamei .…”
Section: Resultsmentioning
confidence: 99%
“…The a* values of all groups were negative (-a*); this may be due to the processing, since the bleeding was done soon after slaughtering the fish, leaving the meat less red, as well as to the analysis, which was performed on the inside part of the fillet. Some authors have also found negative a* values and attributed them to the processing, which did not leave enough red muscle in the samples (Zhao et al 2016).…”
Section: Color Characteristicsmentioning
confidence: 99%